High Endocannabinoid Tone In LFABP -/- Mice Drives Fat Intake and Preference. (7th June 2021) - Amado, Nicholas; Breslin, Paul; Storch, Judith
Abstract: Objectives: Our objective was to understand if LFABP -/- mice display a higher preference for a high fat, high palatable food over Wild-type (WT) mice and if this preference is due to alteration of oral fatty acid detection thresholds by endocannabinoids. Methods: For the first experiment, 6 mice (3 WT and 3 LFABP -/-) were given access to a high-fat cake frosting (Crisco/sugar mixture) for 5 minutes and frosting intake was recorded. This was done at the same time each day and repeated 3 times. For the second experiment, we conducted a 24-hour 2 bottle preference test of a control versus stearic acid solution in 5 WT and 5 LFABP -/- mice. The 2 bottles were switched at 12 hours to minimize side-preference. Preference was defined as the percentage of intake of fatty acid solution over total intake. Results: Our preliminary results showed that 1) the LFABP KO mice consumed more high-fat frosting during a brief access test and 2) the WT mice significantly preferred the control over the stearic acid solution, whereas the LFABP -/- mice showed no difference in preference between the two bottles. Conclusions: These results suggest that elevated endocannabinoid tone contributes to preference for frosting, in part, by modulating oral fatty acid detection thresholds. Changes in oral detection thresholds of taste stimuli are known to affect consumption of the stimuli; the present data support this idea for 'fat-taste' as well. This has important implications for the overconsumption of highly palatable food in our society. Funding Sources: This research was supported by NIH NIDCD R01 014286 to PASB Co-PI, USDA NJ Hatch NJ14120 to PASB and NIH NIDDK R01 38389 and USDA NJ Hatch NJ14115 to JS.